The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/icvts/ivac001
|View full text |Cite
|
Sign up to set email alerts
|

A novel Fontan Y-graft for interrupted inferior vena cava and azygos continuation

Abstract: OBJECTIVES To evaluate the hemodynamicdynamic advantage of a new Fontan surgical template that is intended for complex single-ventricle patients with interrupted inferior vena cava-azygos and hemi-azygos continuation. The new technique has emerged from a comprehensive pre-surgical simulation campaign conducted to facilitate a balanced hepatic flow and somatic Fontan pathway growth after Kawashima procedure. METHODS For 9 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Pre-surgical simulations carried out on 9 individuals in Lashkarinia et al 's Y transplant fontan study [13] revealed that flow from the hepatic veins (HEP) was not reaching the target lung. The HEP flow to the target lung was dramatically increased by the innovative Y-graft template.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-surgical simulations carried out on 9 individuals in Lashkarinia et al 's Y transplant fontan study [13] revealed that flow from the hepatic veins (HEP) was not reaching the target lung. The HEP flow to the target lung was dramatically increased by the innovative Y-graft template.…”
Section: Discussionmentioning
confidence: 99%
“…Total energy loss (EL) is an emerging clinical hemodynamic parameter representing the pulsatile energy lost due to the blood flow as it flows through the cardiovascular component volume. It is utilized routinely in the pre-surgical planning of Fontan conduits [ 6 ]. 4D flow MRI is a useful tool to estimate the EL in the Fontan system and can explain the cause of FF [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a case with FF presenting with severe ascites. Although echocardiography and cardiac catheterization show normal findings, an interventional approach was initiated and judged according to the comparative EL levels calculated with 4D flow MRI [ 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the population of late survivors with Fontan circulation continues to grow and donor organ shortages persist, the management of Fontan failure has become a signi cant clinical challenge, and innovative strategies are urgently required [15]. Attempts aimed at addressing the Fontan paradox have primarily focused on optimizing the TCPC anatomy to improve blood energetics through novel surgical pathways, such as Y-grafts [16][17][18][19][20][21]. These modi cations, however, fail to address the physiologic de cit of a ventricle as the right-side driving pump and thus have little impact on the Fontan outcomes [22].…”
Section: Introductionmentioning
confidence: 99%